2007
DOI: 10.1159/000112597
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin, Body Weight and Inflammatory Parameters in Chronic Hemodialysis Patients: A Three-Year Longitudinal Study

Abstract: Backgrounds and Aims: The present study aimed at making prospective longitudinal measurements of nutritional and inflammatory parameters to determine whether nutritional and inflammatory status decline or increase over time in a cohort of prevalent hemodialysis patients, and to evaluate which factors influence eventual changes. Patients: 64 hemodialysis patients were followed at 0, 3, 6, 9, 12, 15, 18, 21, 24, 27, 30, 33, and 36 months. At each follow-up visit, dry body weight, serum albumin, serum total chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
(44 reference statements)
5
6
0
Order By: Relevance
“…Whereas serum albumin was a weak predictor of nutritional status defined by SGA score, associations between serum albumin and other markers of nutritional status, such as handgrip strength and LBM, were even weaker. Our data showing this clear lack of value of serum albumin as a predictor of nutritional status ( Figure 3, A and B) correspond to and extend previous results reported by us (28) and others (29) showing that serum albumin is a poor predictor of nutritional status in dialysis patients. The current results support views expressed by The results show that the added value of using serum albumin over and above prediction obtained by using only information about age, sex, and comorbid diabetes and CVD is negligible.…”
Section: Discussionsupporting
confidence: 92%
“…Whereas serum albumin was a weak predictor of nutritional status defined by SGA score, associations between serum albumin and other markers of nutritional status, such as handgrip strength and LBM, were even weaker. Our data showing this clear lack of value of serum albumin as a predictor of nutritional status ( Figure 3, A and B) correspond to and extend previous results reported by us (28) and others (29) showing that serum albumin is a poor predictor of nutritional status in dialysis patients. The current results support views expressed by The results show that the added value of using serum albumin over and above prediction obtained by using only information about age, sex, and comorbid diabetes and CVD is negligible.…”
Section: Discussionsupporting
confidence: 92%
“…Of interest is the observation that adverse changes in body composition parameters occur over time, supporting the hypothesis that end-stage renal disease is associated with wasting as proposed in some [43,44] but not all [45] of the previous studies. The results of our study were consistent with those reported by Johansen et al [43] who did not find significant changes in any of the biochemical markers with time, but a significant reduction in phase angle over 1 year follow up was evident in prevalent HD patients.…”
Section: Discussionsupporting
confidence: 56%
“…Bossola et al (48) found stable levels of CRP over 3 years of observation in a cohort of prevalent hemodialysis patients. In contrast, Kaysen et al (43) showed that the levels of CRP and other acute-phase proteins varied considerably over time in 37 participants of the HEMO study.…”
Section: Discussionmentioning
confidence: 95%